Analisis faktor pelaksanaan Continuity Of Care (COC) pada ibu terhadap kejadian Wasting pada balita di Puskesmas Sungai Pinang Kab Ogan Ilir Tahun 2023 - murniati, murniati; Amlah, Amlah; Rahmawati, Eka (NHM PRESS, 2023)
Nutritional problems are disturbances in several aspects of individual and/or community well-being caused by the non-fulfillment of the need for nutrients obtained from food. Wasting is one of the nutritional problems in Indonesia. The incidence of wasting in Indonesia has decreased in recent years. the results of the Indonesian nutritional status survey (SSGI) in 2020 the incidence of wasting is 7.4%, and in 2021 it will be 7.1% and will increase in 2022 by 7.7%. Meanwhile, the percentage of underweight children aged 0-59 months in South Sumatra in 2021 was 2.1%, a decrease compared to 2020 (4.3%). The purpose of this study was to determine the relationship between the history of ANC examinations, the status of the mother's KEK during pregnancy, exclusive breastfeeding simultaneously with the incidence of wasting at the Sungai Pinang Health Center. Type and Design Research is quantitative using an analytic survey method with an approachcross sectional. The population in this study were all mothers who checked their toddler's health at the Sungai Pinang Health Center, totaling 410 respondents. The sample used amounted to 74 respondents. Sampling using accidental sampling technique. The results of univariate analysis were obtained from 79 respondents. Resultsunivariate analysis of 79 respondents there were 6 respondents (7.6%) who experienced wasting and those who did not were 73 respondents (92.4%). The results of the chi-square statistical test variable history of ANC visits ρ value = 0.013, variable history of maternal CED during pregnancy ρ value = 0.001 and exclusive breastfeeding ρ value = 0.007 less than α = 0.05 indicating there is a significant relationship between history of ANC visits , History of maternal CED during pregnancy and exclusive breastfeeding with wasting incidents at the Puskesmas Sungai Pinang,